1999
DOI: 10.2136/sssaj1999.03615995006300020016x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Determining Bulk Densities of Rocky Forest Soils

Abstract: Measurement of forest soil bulk density is often hampered by coarse fragments. In this study, five methods to determine total and fine bulk density and coarse‐fragment content of a rocky forest soil in western Montana were evaluated. Two methods of core sampling (small and large diameter cylinders), two methods of soil excavation and volume determination (water and polyurethane foam), and a nuclear source moisture gauge were tested at two depths (0–10 cm and 10–20 cm) on a soil with a 35% slope and 45% rock co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(71 citation statements)
references
References 0 publications
3
67
1
Order By: Relevance
“…Th e forest soil bulk density in our study was slightly lower than forest soil values reported by Page-Dumroese et al (1999) for the foam and radiation methods in which the authors found bulk densities to be 1.10 and 1.24 Mg m −3 at 0 to 10 cm and 1.11 to 1.21 Mg m −3 at 10 to 20 cm. Th e Page-Dumroese et al (1999) study found little diff erence in bulk density values between the foam and radiation methods in a rocky forest soil.…”
Section: Resultscontrasting
confidence: 88%
“…Th e forest soil bulk density in our study was slightly lower than forest soil values reported by Page-Dumroese et al (1999) for the foam and radiation methods in which the authors found bulk densities to be 1.10 and 1.24 Mg m −3 at 0 to 10 cm and 1.11 to 1.21 Mg m −3 at 10 to 20 cm. Th e Page-Dumroese et al (1999) study found little diff erence in bulk density values between the foam and radiation methods in a rocky forest soil.…”
Section: Resultscontrasting
confidence: 88%
“…However, as stated by several authors (Page-Dumroese et al, 1999), all methods differ in accuracy (success in estimating the true value of rb), precision (clustering of sample estimates about their own mean), and bias (the systematic distortion of estimates for the true value). In the present work, the excavation method gave less precision (higher variation) for both soils analyzed, which was attributed to non-uniformity in the original samples.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-and post-harvest (at 1 and 5 years) collection of soil strength and bulk density were conducted in a manner that conformed to established published protocols (i.e., Blake and Hartge 1986;Muller and Hamilton 1992;Lichter and Costello 1994;Page-Dumroese et al 1999), but were necessarily different at each installation because of differences in rock-fragment amounts and size, sampling equipment, or timing (Table 2). Bulk density samples were collected from the 0-10, 10-20, and 20-30 cm depths on the Malbis, Freest (all three sites from Powers (2006)), Missouri, Goldsboro, Council, Ottawa, Huron-Manistee, and Chippewa sites; at 0-10 and 10-20 cm depths on the Nemagos Lake site; and at 0-20 cm depth on the Topley site.…”
Section: Methodsmentioning
confidence: 99%
“…Rock-fragment content was measured by either field estimates or gravimetric laboratory mass. Total bulk density was corrected for rock-fragment content as necessary (Andraski 1991;Page-Dumroese et al 1999). Soil texture was determined using established published protocols (i.e., Gee and Bauder 1986).…”
Section: Methodsmentioning
confidence: 99%